Alarming increase in ketoacidosis in children and adolescents with newly diagnosed type 1 diabetes during the first wave of the COVID‐19 pandemic in Israel. Issue 1 (14th December 2021) - Goldman, Shira; Pinhas‐Hamiel, Orit; Weinberg, Adi; Auerbach, Adi; German, Alina; Haim, Alon; Zung, Amnon; Brener, Avivit; Strich, David; Azoulay, Erez; Levy‐Khademi, Floris; Ludar, Hanna; et al.
Abstract: Objective: To evaluate the incidence and severity of ketoacidosis (DKA) at type 1 diabetes diagnosis during the first wave of the coronavirus disease 2019 (COVID‐19) pandemic in Israel. Research Design and Methods: A population‐based study the product of a national collaboration of Israeli pediatric diabetes centers investigated the presentation of childhood‐onset type 1 diabetes. The frequencies of DKA and severe DKA observed during the COVID‐19 period from March 15, 2020 (commencement of the first nationwide lockdown) until June 30, 2020 were compared with the same periods in 2019, 2018, and 2017 using multivariable logistic regression, adjusting for age, sex, and socioeconomic position. Results: During the COVID‐19 period, DKA incidence was 58.2%, significantly higher than in 2019 (adjusted OR [aOR] 2.18 [95% CI, 1.31–3.60], P = 0.003); 2018 (aOR 2.05 [95% CI, 1.26–3.34], P = 0.004); and 2017 (aOR, 1.79 [95% CI, 1.09–2.93], P = 0.022). The incidence of severe DKA was 19.9%, significantly higher than in 2018 (aOR, 2.49 [95% CI, 1.20–5.19], P = 0.015) and 2017 (aOR, 2.73 [95% CI, 1.28–5.82], P = 0.009). In 2020, admissions and duration of stay in the intensive care unit were higher than in previous years ( P = 0.001). During the COVID‐19 pandemic, children aged 6–11 years had higher incidences of DKA (61.3% vs. 34.0%, 40.6%, and 45.1%, respectively, P = 0.012), and severe DKA (29.3% vs. 15.1%, 10.9%, and 5.9%, respectively, P = 0.002). Conclusions: The dramatic increase in DKA at presentation of childhood‐onset type 1 diabetes during the COVID‐19 pandemic mandates targeted measures to raise public and physician awareness.